Anaphylatoxin-induced histamine release with human leukocytes: studies of C3a leukocyte binding and histamine release. - Glovsky, M M (1979)
Purified human C3a and synthetic COOH-terminal peptides of C3a, i.e., a pentapeptide, Leu-Gly-Leu-Ala-Arg (5R), and an octapeptide, Ala-Ala-Ala-Leu-Gly-Leu-Ala-Arg (8R) induced histamine release from human basophil granulocytes. On a molar basis, 5R was one-tenth and 8R was one-fifth as active as C3a in causing histamine release. It was found that 125I-C3a binds to whole leukocytes, interacting with both mononuclear cells and neutrophils and the binding was inhibited by preincubation of cells with unlabeled C3a, but not by C5a. 5R and 8R also inhibited the binding of 125I-C3a to the cells. However, on a molar basis, 2,000 times more 8R or 6,000 times more 5R is required for 50% inhibition of 125I-C3a binding as compared with native C3a. Autoradiography of cells using 125I-C3a and 125I-C5a showed preferential binding of 125I-C3a to eosinophils and basophils, whereas 125I-C5a binds primarily to neutrophils and eosinophils and to a lesser extent to basophils. The preferential binding of C3a and C5a to different cell types may herald significance related to their physiological functions.